Monoxide carbon frequency shift as a tool for the characterization of TiO2 surfaces: Insights from first principles spectroscopy - Lustemberg, Pablo German (2013)
The adsorption and vibrational frequency of CO on defective and undefective titanium dioxide surfaces is examined applying first-principles molecular dynamics simulations. In particular, the vibrational frequencies are obtained beyond the harmonic approximation, through the time correlation functions of the atomic trajectories. In agreement with experiments, at low CO coverages we find an upshift in the vibration frequency with respect to the free CO molecule, of 45 and 35 cm-1 on the stoichiometric rutile (110) and anatase (101) faces, respectively. A band falling 8 cm-1 below the frequency corresponding to the perfect face is observed for the reduced rutile (110) surface in the low vacancy concentration limit, where the adsorption is favored on Ti4+ sites. At a higher density of defects, adsorption on Ti3+ sites becomes more stable, accompanied by a downshift in the stretching band. In the case of anatase (101), we analyze the effect of subsurface oxygen vacancies, which have been shown to be predominant in this material. Interestingly, we find that the adsorption of CO on five coordinate Ti atoms placed over subsurface vacancies is favored with respect to other Ti4+ sites (7.25 against 6.95 kcal/mol), exhibiting a vibrational redshift of 20 cm-1 . These results provide the basis to quantitatively assess the degree of reduction of rutile and anatase surfaces via IR spectroscopy, and at the same time allow for the assignment of characteristic bands in the CO spectra on TiO2 whose origin has remained ambiguous.